The choice of parameters of communication devices of computer networks - Савченко, A. C. (Problems of Informatization and Control, 2007)
In the article the choice of parameters dependent switching equipment and structure characteristics of computer network traffic. Analytical dependence for utility network bandwidth depending on the intensity of traffic, waiting time and justified demands to the required size of the buffer memory switching equipment